On a new integration scheme for von-Mises plasticity with linear hardening - Auricchio, Ferdinando; Beirão da Veiga, Lourenço (International journal for numerical methods in engineering, 2003)
Limiting the discussion to an associative von‐Mises plasticity model with linear kinematic and isotropic hardening, we compare the performance of the classical radial return map algorithm with a new integration scheme based on the computation of an integration factor. The numerical examples clearly show the improved accuracy of the new method. Copyright © 2003 John Wiley & Sons, Ltd.